Modeling and controlling nanoscale patterns formed by bombardment with a broad ion beam - Harrison, Matthew Paul, author; Bradley, R. Mark, advisor; Gelfand, Martin, committee member; Shipman, Patrick, committee member; Field, Stuart, committee member (Colorado State University. Libraries, 2017)
For over half a century it has been known that bombarding a solid surface with a broad ion beam can produce periodic nanoscale structures. Given the virtually limitless promise of nanotechnology, the potential of ion bombardment to produce nanopatterned surfaces over large areas in a simple and economical way has attracted substantial interest. In the decades since its discovery, there has been a wealth of experimental and theoretical work examining the phenomenon in detail, with the eventual goal of using ion beam sputtering (IBS) to produce useful nanostructures. Despite the body of work, there are many open questions and unsurmounted challenges remain- ing. In this thesis, I present work that I have conducted in collaboration with my advisor, Mark Bradley, with whom I addressed some of these challenges. I show how we developed a formalism which connects information about single ion impacts to the evolution of a surface which sustains > 1016 such impacts per square centimeter. We have also produced theoretical results for the case of a binary material being bombarded while rotated azimuthally, with some unexpected findings. I also discuss some very exciting theoretical predictions for the case in which an elemental target is bombarded while the polar angle of ion incidence periodically changes. In this case we find the temporal driving can induce a surface pattern which is nearly perfectly periodic in the long time limit. I also discuss our work on using templated surfaces in conjunction with IBS to produce ii high quality blazed gratings and multilayer blazed gratings. This work is the subject of a current collaboration with Carmen Menoni and her students.
Keywords: ion; pattern; bombardment; PDE; nanoscale